2018
DOI: 10.1111/1471-0307.12574
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotic cultures on the organic acid content, texture profile and sensory attributes of Tulum cheese

Abstract: The aim of this study was to evaluate the effects of Lactobacillus acidophilus and Bifidobacterium animalis subsp. lactis on the organic acid, texture profile and sensory attributes of Tulum cheese. The acidity of sample increased throughout the storage. Storage time influenced the organic acid content of samples (P < 0.0001). Lightness decreased while redness increased (P < 0.05). Cohesiveness decreased during storage, whereas the values of all other Texture Profile Analyses (TPA) parameters increased. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 48 publications
(72 reference statements)
1
23
0
2
Order By: Relevance
“…Dn the other hand, although the amount of medium and long chain fatty acids is quantitatively important, they have no contribution to the formation of cheese aroma (Attaie & Richter, 1996). Also, the probiotic culture added did not affect flavour scores of Tulum cheese (Tomar, 2018).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Dn the other hand, although the amount of medium and long chain fatty acids is quantitatively important, they have no contribution to the formation of cheese aroma (Attaie & Richter, 1996). Also, the probiotic culture added did not affect flavour scores of Tulum cheese (Tomar, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…These results show that adding L. acidophilus and MOX cultures did not produce defects in sensory scores and could even improve the organoleptic characteristics of Erzincan Tulum cheese. Similarly, Minervini et al (2012), Cuffia et al (2018) and Tomar (2018) reported that the addition of probiotic strains improved the sensory properties of cheese during the ripening.…”
Section: Samplesmentioning
confidence: 89%
See 3 more Smart Citations